An anti-racism methodology: The Native Sons and Daughters and racism against Asians in Nanaimo, British Columbia, Canada - Ian G. Baird (2018)
© 2017 Canadian Association of Geographers / L'Association canadienne des géographes Over the past number of years there has been increased interest in racism and anti-racism amongst geographers. This paper focuses on one type of anti-racism methodology that relates to critically interrogating my own white colonial settler ancestors and particularly the institutions and structures of which they were a part, and using those understandings to resist the contemporary increase in white supremacy and anti-Asian racism. It also seeks to demonstrate the links between anti-racism and decolonization. Particularly, I examine the Native Sons and Daughters of British Columbia, Canada, in the Nanaimo city area, where my great-grandparents from northern England and Scotland settled as working-class miners at the beginning of the 20th century. I examine white working-class settler racism against Asians, especially as practiced against Chinese and Japanese immigrants. While I do not argue that this is the only or even the most important type of anti-racism methodology, this sort of research and associated production of knowledge can be useful in resisting present-day anti-Asian racism, even though I acknowledge that I am still embedded in colonial structures of racism and white privilege.